Alteraciones visuales y oculares en niños y jóvenes con diabetes mellitus (2022)
Introduction: Diabetes is defined as a group of metabolic diseases characterized by hyperglycemia, associated with multifactorial damage to different organs, including the eyeball, thus allowing the identification and early diagnosis of visual and ocular alterations, taking into account the findings in the anterior and posterior segment, especially in the care of children and young people with Type 1 Diabetes Mellitus. Methodology: An exhaustive search of scientific articles found in different search engines such as: Pubmed was carried out. Science Direct, Proquest, Scielo, American Academy Of Ophthalmology, etc, with a publication date of less than 10 years, in English and Spanish. Results: Visual and ocular alterations were found, both in the anterior and posterior segments in children and young people with type I diabetes mellitus; being more prevalent the decrease in vascular density in the superficial and deep capillary plexus of the retina corresponding to 10%, in the same way it was found that the structure that is most affected in the anterior segment is the lens with a percentage of 20% and 15% of refractive errors pertaining to visual function. Conclusions: Taking into account the progressive prevalence of DM1, the approach and intervention of new research is necessary to improve the prognosis of visual and ocular health in this age group.